Acoustophoretic Liquefaction for 3D Printing Ultrahigh‐Viscosity Nanoparticle Suspensions. Issue 7 (5th January 2022) - Liu, Zheng; Pan, Wenyang; Wang, Kaiyang; Matia, Yoav; Xu, Artemis; Barreiros, Jose A.; Darkes‐Burkey, Cameron; Giannelis, Emmanuel P.; Mengüç, Yiğit; Shepherd, Robert F.; Wallin, Thomas J.
Abstract: An acoustic liquefaction approach to enhance the flow of yield stress fluids during Digital Light Processing (DLP)‐based 3D printing is reported. This enhanced flow enables processing of ultrahigh‐viscosity resins (μapp > 3700 Pa s at shear rates γ ˙ = 0.01 s –1 ) based on silica particles in a silicone photopolymer. Numerical simulations of the acousto–mechanical coupling in the DLP resin feed system at different agitation frequencies predict local resin flow velocities exceeding 100 mm s –1 at acoustic transduction frequencies of 110 s –1 . Under these conditions, highly loaded particle suspensions (weight fractions, ϕ = 0.23) can be printed successfully in complex geometries. Such mechanically reinforced composites possess a tensile toughness 2000% greater than the neat photopolymer. Beyond an increase in processible viscosities, acoustophoretic liquefaction DLP (AL‐DLP) creates a transient reduction in apparent viscosity that promotes resin recirculation and decreases viscous adhesion. As a result, acoustophoretic liquefaction Digital Light Processing (AL‐DLP) improves the printed feature resolution by more than 25%, increases printable object sizes by over 50 times, and can build parts >3 × faster when compared to conventional methodologies. Abstract : Acoustophoretic‐liquefaction Digital Light Processing (AL‐DLP) permits manipulation of resin rheology during 3D printing. Acoustic transduction reduces the viscosity of nanopartice suspensions by up to three orders of magnitude to promote resin recirculation and reduce viscous adhesion. Consequently, AL‐DLP improves resolution (>25%), increases printable area (≈50 × ), and reduces build times (>3 × faster) when compared to conventional methods for printing composite.